Carbon Partitioning in Potted Post-V eraison Vitis vinifera L. CV. Riesling Vines: Effect of Dormant Cane Length - Stewart, W.P.; Freeman, B.M.; Dick, J.K. (South African Journal of Enology and Viticulture, 2017)
To investigate the movement of photoassimilates within a wine canopy, potted Vitis vinifera L. cv. Riesling grapevines were pruned to two different dormant cane lengths of 100 mm and 900 mm. Shoots on these canes were vertically trained with one non-fruitbearing shoot growing from the apical node and one fruit-bearing shoot growing from the basal node for each treatment .. Known quantities of 1'C02 were loaded into the source leaf located at leaf node position 10 on the apical shoot. Bi-directional translocation of 14C photoassimilates was demonstrated. Minimal translocation of 1'C photoassimilates from source leaves on non-fruit-bearing shoots was directed towards the clusters located on the lower shoot. The non-fruit-bearing shoots are, however, contributing to the carbohydrate reserves in the roots, where an allocation of over 50% of the exported "C photoassimilates to the roots was demonstrated in both treatments.